Combined LASER and femoral approach to remove a previous failure of Riata lead extraction. Issue 9 (20th July 2017) - Dello Russo, Antonio; Fassini, Gaetano Michele; Conti, Sergio; Vettor, Giulia; Casella, Michela; Tundo, Fabrizio; Roberto, Maurizio; Grillo, Francesco; Alamanni, Francesco; Tondo, Claudio
Key Clinical Message: Transvenous extraction of Riata lead could be a challenging procedure due to insulation failure and conductor cables' externalization through the eroded outer insulation. In this case, a complete lead extraction was achieved through a combined LASER and femoral approach because of the massive conductors' externalization. Abstract : Transvenous extraction of Riata lead could be a challenging procedure due to insulation failure and conductor cables' externalization through the eroded outer insulation. In this case, a complete lead extraction was achieved through a combined LASER and femoral approach because of the massive conductors' externalization.